2017
DOI: 10.1016/j.copsyc.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Stress and child development: a review of the Family Stress Model

Abstract: In the present report, we provide an illustrative review of the Family Stress Model (FSM) framework [1] to understand how family stress influences children across development in physical, social-emotional, and cognitive domains. We note that the FSM as a theory has evolved through inspection of: (a) new explanatory pathways (mediators); (b) factors that moderate FSM pathways; and (c) joint tests of competing models. Also important, most researchers cited in this review used longitudinal designs to test the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

60
604
2
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 722 publications
(737 citation statements)
references
References 39 publications
60
604
2
13
Order By: Relevance
“…Psychological and affective disorders often strongly influence parents' affective interactions and responses, and consequently, poor mental health spills over into marital and coparenting relationships as well as parent–child interactions (Downey & Coyne, ; Goodman, ; Suchman, DeCoste, & Dias, in press). As couples struggle to make ends meet, their interactions tend to become more hostile and conflicted; in turn, they can withdraw from each other (Conger & Elder, ; Masarik & Conger, ). Parents' psychological distress and conflict are linked with parenting practices that are, on average, more punitive, harsh, inconsistent, and detached, as well as less nurturing, stimulating, and responsive to children's needs.…”
Section: The Challenge Of Caring For Childrenmentioning
confidence: 99%
“…Psychological and affective disorders often strongly influence parents' affective interactions and responses, and consequently, poor mental health spills over into marital and coparenting relationships as well as parent–child interactions (Downey & Coyne, ; Goodman, ; Suchman, DeCoste, & Dias, in press). As couples struggle to make ends meet, their interactions tend to become more hostile and conflicted; in turn, they can withdraw from each other (Conger & Elder, ; Masarik & Conger, ). Parents' psychological distress and conflict are linked with parenting practices that are, on average, more punitive, harsh, inconsistent, and detached, as well as less nurturing, stimulating, and responsive to children's needs.…”
Section: The Challenge Of Caring For Childrenmentioning
confidence: 99%
“…Studies have found a number of reasons that might explain the pathways or the connections between fragile families and lower child well‐being (Masarik & Conger, ; Osborne & McLanahan, ; Ribar, ; Waldfogel et al., ). Probabilistically, these factors also reduce the likelihood that the development of the psychological self will progress along healthy lines.…”
Section: Relational Developmental Metatheory and The Early‐in‐life Ormentioning
confidence: 99%
“…The Family Stress Model (FSM; Conger, Conger, & Martin, 2010) has consistently demonstrated that economic hardship results in greater economic pressure, which impairs the mental health and parenting behaviors of adult family members. Economic stress can result in conflict between caregivers that spills over to the parent-child relationship and thereby results in more negative outcomes for children (e.g., Conger et al, 2010;Conger et al, 2012;Masarik & Conger, 2016) and adolescents (e.g., Conger et al, 1991;Landers-Potts et al, 2015).…”
Section: Factors Affecting Coping In Adolescencementioning
confidence: 99%